TRADISI MASYARAKAT JAWA DAN MADURA SEBAGAI BENTUK AKULTURASI BUDAYA PESISIRAN DI DESA BUKO KABUPATEN DEMAK - Mahfudlah Fajrie; Khoirul Muslimin (Sosial Budaya, 2019)
In Buko village Demak Regency, has a different cultural community, namely the Javanese people as indigenous people and the Madurese community as migrants. This cultural difference is what led to the process of cultural acculturation. Coastal culture related to coastal traditions over time, technological developments and modernization are shifting. The purpose of this study was to find out and analyze the traditions of Javanese and Madurese coastal communities that still exist and are carried out, the processes and forms of acculturation of Javanese and Madurese culture in Buko Village. So that it can prove that cultural differences do not make the basis for the existence of division, instead it makes unity. Type research ethnographic approach, informants with purposive sampling technique, data collection by observation, interviews and documentation. Data analysis uses cultural theme. Coastal traditions between the Javanese and Madurese communities in Buko Village that are still being carried out are nanggap wayang, mitoni, ngapati and sumur tiban as a tradition of Javanese people, the tradition of Madurese people is the istigosah and activities of the Laskar Madura community. Javanese and Madurese traditions in Buko Village occur cultural acculturation through blind acculturation because people with different cultures in this case Java and Madura live close to each other and cultural patterns are learned accidentally. One tradition as a form of cultural acculturation between Javanese and Madurese communities is manaqib, this tradition has the purpose of strengthening ties and increasing unity between Javanese and Madurese people who have different cultures and languages.